Integrated Child Development Services (ICDS) Scheme in India - a tired horse or an ignored one. An evaluation in a tribal district of Maharashtra, India - Michi Monya (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Introduction: The lives of children and women are the true indicators of the strength of communities and nations. UNICEF considers Child Mortality rate as the single best indicator of social development and well-being. Integrated Child Development Services (ICDS) Scheme is one of the largest maternal and child health programs representing a symbol of India's commitment to its children. The anganwadi centre (AWC) is the grassroot functionary of ICDS and the program is executed through dedicated cadre of female workers named Anganwadi workers (AWWs). Still India records high infant, child and maternal mortality rates. Also, frequent malnutrition related deaths in the state of Maharashtra has raised questions on the implementation of these programmes. This study was conducted to evaluate the functionality of Anganwadi Centres in terms of infrastructure and logistics and assess the satisfaction of Anganwadi workers. Methodology: This was a community based cross-sectional descriptive study in the tribal district of Palghar in Maharashtra. Universal sample of all the Anganwadi centres under the randomly selected PHC was adopted for the study. Data for the study was collected by using personal interview technique with the help of a semi structured questionnaire and by self-observation using a standard checklist. The data collected was analysed using appropriate descriptive statistics with the help of Epi info. Result: Only just about half of the AWCs were functioning in their own building. Among infrastructure and logistics, registers for record keeping was found to be most deficient (88.9%) followed by presence of electricity and baby weighing machine (77.8%). Availability of separate kitchen and storeroom and regularity of supplementary nutrition supply was seen deficient in 69.4% of AWCs. Growth card was the most available amenity (100%) followed by adult weighing machine which was present in 91.7% of AWCs and drinking water facility in 86.1%. Toilet was present in only about half of the AWCs studied. Among the various problems accounting for poor job satisfaction among AWWs, some of the prominent were, lack of own anganwadi building, inadequate space for activities, lack of teaching materials, problems in eliciting the Supplementary Nutrition Programme (SNP) due to inadequacy or irregularity of the supplementary nutrition supply, and absence of separate kitchen. Other problems faced were low government and community involvement, increased workload and a modest honorarium. Conclusion: Studies conducted across the country, has observed that various factors contributed to the efficient service delivery of ICDS. Our study exposes some key factors that affect the effective implementation of the scheme and the felt needs of its implementers at the grass root level.